Changing Clinical pattern of Rheumatic Fever at Peshawar, (Pakistan) - Gandapur, Amin Jan; Rahim, Fazal; Asghar, Asghar H.; M., Shafique; Hameed, Abdul; Khawar, Nadeem (Journal of Postgraduate Medical Institute, 2011)
Rheumatic fever (RF) still remains a common problem and an important cause of morbidity and mortality in our children. The purpose of this study was to know the change in clinical profile and presentation of RF, determine its hospital prevalence and assess the magnitude of problem at Peshawar. We did a study on RF from 1986 - 87 in LRH, Peshawar. Significant data on prevalence, clinical profile, recurrence rate and the types of valvular lesions in carditis was collected (unpublished). during 1999 - 2000, after 12 years and in same city, we conducted another prospective study on RF in one of the two units of Khyber Teaching Hospital. 35 children were documented and studied. Rhumatic fever has shown a decline in at least hospital prevalence in our setup. Polyrthritis was more common than carditis in the latest study, a trend more often seen in developed world.